Increasing Upper Body Strength of Wrestling Athletes through Bulgarian Bag Exercise - Maki, M. Tobibi; Berliana, Berliana; Nurjaya, Dede Rohmat; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Wrestling is a fighting sport that requires strength, especially in the upper body. However, the strength training carried out so far is still conventional and monotonous, while literature studies have provided various other, more modern and effective alternatives for strength training, one of which is the Bulgarian Bag. This study aims to examine the effect of training using Bulgarian Bag on the strength of the upper body of wrestling athletes. Research on Bulgarian Bag itself is still relatively small because Bulgarian Bags themselves are still relatively new. The research method used is an experimental method with a pre-test post-test control group design. The subjects of this study were wrestling athletes in West Bandung Regency with 10 male athletes taken by total sampling from the population. The research instrument used was a dynamic endurance hand grip strength test and a push up test which was given 2 times to the subject. Subjects were divided into two groups, namely the experimental group which was given the Bulgarian Bag exercise and the control group which was given the conventional exercise. T-test using SPSS version 24 was performed as data analysis in this study. The results showed that the Bulgarian Bag exercise had a significant effect on increasing the strength of the upper extremity of wrestling athletes. So it can be concluded that training using Bulgarian Bags can be used as the right choice to increase the strength of the upper body of wrestling athletes. The authors suggest integrating these exercises into a structured strength training program.